2022
DOI: 10.1038/s41598-022-10553-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and geographical delineation of zoonotic vector-borne helminths of canids

Abstract: Several zoonotic vector-borne helminths (VBHs) infesting canids cause serious veterinary and medical diseases worldwide. Increasing the knowledge about their genetic structures is pivotal to identify them and therefore to settle effective surveillance and control measures. To overcome the limitation due to the heterogeneity of large DNA sequence-datasets used for their genetic characterization, available cytochrome c oxidase subunit 1 (cox1) (n = 546) and the 12S rRNA (n = 280) sequences were examined using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
3
2
0
Order By: Relevance
“…Most sequences (75%) formed the Di1 haplotype, which is in agreement with a previous study using mt sequences of COI and 12S rDNA derived from the GenBank, which showed that 272 out of the 277 D. immitis sequences (98%) formed a dominant haplotype [ 47 ]. In total, only five haplotypes were delineated based on these two mt markers from sequences from 26 countries [ 47 ], which is much lower than in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Most sequences (75%) formed the Di1 haplotype, which is in agreement with a previous study using mt sequences of COI and 12S rDNA derived from the GenBank, which showed that 272 out of the 277 D. immitis sequences (98%) formed a dominant haplotype [ 47 ]. In total, only five haplotypes were delineated based on these two mt markers from sequences from 26 countries [ 47 ], which is much lower than in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Most sequences (75%) formed the Di1 haplotype, which is in agreement with a previous study using mt sequences of COI and 12S rDNA derived from the GenBank, which showed that 272 out of the 277 D. immitis sequences (98%) formed a dominant haplotype [ 47 ]. In total, only five haplotypes were delineated based on these two mt markers from sequences from 26 countries [ 47 ], which is much lower than in the current study. One of the reasons could be that the haplotypes in the current study were based on the entirety of the combined COI and NADH genes, which offers a broader insight into the genetic diversity of each isolate and better delineation of haplotypes while the sequences used in previous study [ 47 ] covered a fragment of the COI gene.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Given the geographical expansion of dirofilariosis it will be important to monitor the effectiveness of MLs in Europe and the possible emergence of resistance. To date, there is minimal published information on the genetic makeup and diversity of European isolates, with Laidoudi et al [24] finding a single common haplotype present in European samples analyzed. In the current study, we analyze the prevalence of the validated North American SNP markers associated with susceptibility and resistance to MLs in European clinical samples.…”
Section: Introductionmentioning
confidence: 99%